PENGARUH REWARD DAN PUNISHMENT TERHADAP KEDISIPLINAN KINERJA GURU DI YAYASAN ZAID BIN TSABIT - Aulia, Dina; Agung, Syahrum; Wibowo, Agung (PT Naureen Digital Education, 2024)
This research is entitled The Effect of Reward and Punishment on the discipline of teacher performance at the Zaid Bin Tsabit Foundation. The aims of this research are: To determine the effect of reward on the disciplinary performance of teachers at the Zaid Bin Tsabit Foundation, to determine the effect of punishment on the disciplinary performance of teachers at the Zaid Bin Tsabit Foundation, to determine the effect of reward and punishment together on the disciplinary performance of teachers at the Foundation Zaid Bin Tsabit. This research method uses quantitative research with a sample size of 53 people. The results of the research showed that there was no significant influence between reward on the disciplinary performance of teachers at the Zaid Bin Tsabit Foundation, there was a significant influence between punishment on the disciplinary performance of teachers at the Zaid Bin Tsabit Foundation, and there was a significant influence between the reward and punishment variables together at the Zaid Foundation Bin Tsabit.